Age-specific life table of swallowtail butterfly Papilio demoleus (Lepidoptera: Papilionidae) in dry and wet seasons - SUWARNO SUWARNO (Biodiversitas Journal of Biological Diversity, 2012)
Suwarno. 2012. Age-specific life table of swallowtail butterfly Papilio demoleus (Lepidoptera: Papilionidae) in dry and wet seasons. Biodiversitas 13: 28-33. Age-specific life table of Papilio demoleus L. in dry and wet seasons was investigated in the Tasek Gelugor, Pulau Pinang, Malaysia. Development of P. demoleus was observed from January to March 2006 (dry season, DS), April to July 2006 (secondary wet season, SWS), and October to December 2006 (primary wet season, PWS). Survivorship of P. demoleus in the DS was lower than in the SWS and in the PWS. The mortality (qx) of the fifth instar larvae P. demoleus in all seasons was higher than in other stages. Predators, parasitoids, and rainfall were the most important factors of mortality in immature stages of P. demoleus. Predators caused the highest mortality in all stages of P. demoleus, except the pupal stage. Predation in the DS (94.39%) was higher than in the SWS (90.88%) and PWS (84.04%) but no significantly different among the seasons. Meanwhile there was significantly different of mortality caused by parasitoids and the rain among the seasons. Spiders were the important mortality agent in the eggs and young larvae, meanwhile in the older larvae were S. dichotomus and Podisus sp. Ooencyrtus papilioni and Pteromalus puparum were theimportant parasitoids for the eggs and pupae of P. demoleus, respectively. In summary, the season influenced the survivorship of P. demoleus in citrus plantation. P. demoleus had the highest survival in the wet primary season (PWS), while the lowest survival was observed in the dry season (DS).